The Effective Therapy for Drug, Gambling, and Pornography Addicts with a Neurolinguistic Approach - Iskandarsyah Siregar (Britain International for Academic Research (BIAR-Publisher), 2024)
This study investigates the effectiveness of Neurolinguistic Programming (NLP) as a therapeutic intervention for individuals suffering from drug, gambling, and pornography addictions. Recognizing addiction as a complex interplay of cognitive distortions, emotional dysregulation, and maladaptive internal narratives, this research employs a mixed-methods design combining quasi-experimental pretest-posttest analysis with phenomenological inquiry. A total of 45 participants from three Indonesian rehabilitation centers underwent either NLP-based therapy or standard counseling over six weeks. Quantitative results from the Addiction Severity Index (ASI), Cognitive Distortion Scale (CDS), and Language Use Assessment (LUA) revealed statistically significant improvements in the NLP group across all addiction types. Participants exhibited reduced cravings, greater emotional regulation, and shifts in self-narration from passive, deterministic language to agentic, self-aware expressions. Qualitative findings further underscored the therapeutic value of NLP techniques such as submodality shifts, reframing, anchoring, and timeline therapy, which helped participants reprogram internal triggers and traumatic associations. The study concludes that NLP effectively addresses the neurocognitive and linguistic dimensions of addiction, facilitating sustained behavioral change. Its adaptable, experiential, and non-pharmacological nature makes it a promising complement to existing treatment modalities. Further research is encouraged to explore long-term effects and broader clinical integration of NLP in addiction recovery.